Calculation studies on point defects in perovskite solar cells *Project supported by the National Natural Science Foundation of China (No. 61574059), the Shanghai Rising-Star Program (No. 14QA1401500), the Shu-Guang Program (15SG20), and the CC of ECNU. (January 2017) - Han, Dan; Dai, Chenmin; Chen, Shiyou
Abstract: The close-to-optimal band gap, large absorption coefficient, low manufacturing cost and rapid increase in power conversion efficiency make the organic–inorganic hybrid halide (CH3 NH3 PbI3 ) and related perovskite solar cells very promising for commercialization. The properties of point defects in the absorber layer semiconductors have important influence on the photovoltaic performance of solar cells, so the investigation on the defect properties in the perovskite semiconductors is necessary for the optimization of their photovoltaic performance. In this work, we give a brief review to the first-principles calculation studies on the defect properties in a series of perovskite semiconductors, including the organic–inorganic hybrid perovskites and inorganic halide perovskites. Experimental identification of these point defects and characterization of their properties are called for.